Urbanizing with equity consideration - Guanghua Wan; Zhi Luo; Xun Zhang (Asian Development Bank Institute (ADBI), 2017)
Research has not yet been undertaken on the optimal level of urbanization, notwithstanding the pioneering work of Au and Henderson (2006) on optimal urban concentration. This paper develops two-sector general equilibrium models of urbanization, with and without equity consideration, respectively. It is shown that considering equity will result in a higher level of urbanization than otherwise, when urban inequality is sufficiently small or migration costs are sufficiently large. Such a theoretical prediction is confirmed by empirical modeling results using panel data from People's Republic of China (PRC). Provincial governments that paid attention to the inequality issue are found to have higher urbanization levels than those that did not. Finally, we explore possible equity consideration-to-urbanization transmission channels, and empirically establish that equity consideration in PRC (e.g., government initiatives towards combating rural poverty or the urban-rural gap) is positively correlated with road density, which helps reduce migration costs, and with bank lending to the manufacturing sector, which helps enhance the pulling force of migration. Thus, policymakers in the developing world should reverse their prevailing anti-urbanization attitudes and practices that tend to slow down urbanization or restrict rural-to-urban migration.
Keywords: O18; E61; D63; 330; Urbanization; Income inequality; Social welfare function; Optimization